2021
DOI: 10.3389/fimmu.2021.663683
|View full text |Cite
|
Sign up to set email alerts
|

SFRP5 Enhances Wnt5a Induced-Inflammation in Rheumatoid Arthritis Fibroblast-Like Synoviocytes

Abstract: BackgroundTissue derived fibroblast-like synoviocytes (td-FLS) are key actors in pannus formation and contribute to joint destruction and inflammation during rheumatoid arthritis (RA). Several members of the Wnt family, including Wnt5a, may contribute to RA td-FLS activation and can potentially serve as therapeutic targets.ObjectiveThe present work aimed to investigate the expression of Wnt5a signaling elements in RA td-FLS and their potential precursors (fluid derived (fd) FLS and fibrocytes). We also studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…It has been shown that RA SF-FLS release multiple inflammatory cytokines dominated by CCL2 and IL6 without exogenous stimulation (19). This corroborates the findings of previous data showing that RA SF-FLS secrete IL6, IL8, IL1b and CCL2 (17,34). In addition, RA FLS from the intimal lining have been considered primary sources of IL6, as shown by in situ hybridization and immunohistochemistry studies (6).…”
Section: Sf-fls and Inflammationsupporting
confidence: 83%
See 2 more Smart Citations
“…It has been shown that RA SF-FLS release multiple inflammatory cytokines dominated by CCL2 and IL6 without exogenous stimulation (19). This corroborates the findings of previous data showing that RA SF-FLS secrete IL6, IL8, IL1b and CCL2 (17,34). In addition, RA FLS from the intimal lining have been considered primary sources of IL6, as shown by in situ hybridization and immunohistochemistry studies (6).…”
Section: Sf-fls and Inflammationsupporting
confidence: 83%
“…SF-FLS from patients with RA display multiple changes in cell morphology during culture (17,18,34). Under light microscopy, SF-FLS appear elongated with an irregular stellate cell shape during the first few days of culture (16,17).…”
Section: Morphology Of Cultured Sf-flsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it also produces Wnt5a, which promotes osteoclast differentiation [ 131 , 132 ]. The expression of Wnt5a in FLS induces inflammatory cytokines [ 133 , 134 , 135 , 136 ], which activate FLS itself. Recent studies using single-cell analysis have shown that cells in the blood, such as macrophages and lymphocytes, are main sources of TNF-α in the synovium of patients with RA [ 137 ].…”
Section: Pathological Bone Metabolism In Ramentioning
confidence: 99%
“…Fibroblast-like synoviocytes (FLS) is a special group of cells in the synovial tissue. During the pathogenesis of RA, FLS show high proliferation, high invasiveness, and tumor-like changes, which play an important role in the development of RA ( 3 , 4 ). Previous studies have shown that apoptosis and autophagy in FLS are closely related to the development of RA ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%